Exploring Grade 1 teachers’ experiences with teaching reading to Deaf learners in special schools - Mashige, Luyanda (University of the Free State, 2024)
This study aimed at exploring the challenges that teachers encountered when teaching reading to Grade 1 Deaf learners. The study was guided by the following objectives: Exploring how Grade 1 teachers teach reading to Deaf learners in special schools. Establish the challenges Grade 1 teachers experience when teaching reading to deaf and to determine the strategies that Grade 1 teachers use when teaching reading to Deaf learners. In order to achieve the objectives, participants were purposively sampled and were drawn from two selected schools. The sample consisted of four (4) special education teachers for Deaf learners picked from Gauteng province. For this study, two research instruments were used for data generation, namely, semi-structured interviews and classroom observations. The study employed the qualitative method to get the answers to the research question.The finding therefore reveals that Deaf learners learning reading need to be exposed to learning resources which meet their unique reading needs. These resources should be special resources beyond the normal resources used in a regular reading class. It is evident that in order to teach reading to Deaf learners’ teachers should Set Deaf learners up for success by adapting their teaching methods to support their learning.The study found that the major challenges that teachers faced when teaching reading to Deaf learners was that there were not adequate instructions and teaching resources to sufficiently teach reading to these learners. This included specialised guidelines from the curriculum development specialists. Arising from the findings of this study, various recommendations have been made, among which is that Deaf learners learning reading for comprehension skills need to be exposed to learning resources which meet their unique reading needs. These resources should be special resources beyond the normal resources used in a regular reading class. It is evident that in order to teach reading to Deaf learners’ teachers should Set Deaf learners up for success by adapting their teaching methods to support their learning. Moreover, there is a need for in- service training on both education managers and educators in the uses of South African Sign Language. Learners in teacher training institutions wishing to educate Deaf learners need to be provided with South African Sign Language skills before entering schools for the Deaf at a pre-service level.
Dissertation (M.Ed. (Early Childhood Development and Learning))--University of the Free State, 2024
Keywords: Foundation phase teachers; Deaf learners; Inclusive education; Special schools; South African Sign Language; Reading; Social constructivism